Psychotropic drugs for the elderly: Which medical specialties prescribe the most? (Research, Society and Development, 2021)
This study aimed to analyze the profile of the medical specialties of psychotropic prescribers for the elderly assisted by the Unified Health System (SUS) in a medium-sized city in Minas Gerais. This is a descriptive study carried out using secondary data on drug dispensing registered in the Computerized Health System between January and December 2017. For this analysis, the specialty of hiring prescribing doctors informed by the Municipal Health Secretariat was considered. 23.599 dispensations were made for 4.833 elderlies, requested by 194 prescribing doctors. The number of prescriptions by specialty was higher among General Physicians – 8.463 (35.9%), Family Health Strategy Physicians – 6.927 (29.4%) and Psychiatrists - 5.152 (21.8%). Analyzing the average number of prescriptions per professional in each specialty, it was observed that Psychiatrists are the ones who prescribe the most, followed by the Mastologists and by General Surgeons, with averages of 1.717, 957 and 215 prescriptions per professional, respectively. The overall average is 122 prescriptions per specialist. It was concluded that the high frequency of psychotropic medications prescriptions to the elderly by doctors who do not have graduation in psychiatry and/or geriatrics is not a legal or ethical infraction, however, considering the care complexity for the elderly and these medications particularities, from the pharmacotherapy choice to the moment of medication interruption, it is necessary to reflect on the challenges ahead, especially in the scenario of fast Brazilian population aging process and the shortage of geriatric doctors.